Seasonal Change of Physico-Chemical Properties of Thermal Water from Afyonkarahisar Region - Aydingöz1, Mesut; Cemek2, Mustafa; Bulut3, Sait (Asian Journal of Chemistry, 2014)
In this study, physico-chemical properties of water samples seasonally collected from well heads of 14 different hot springs in Afyonkarahisar were determined. In water samples, nitrate and nitrite were analyzed by a spectrophotometer, while 26 elements were analyzed by ICP-OES. Temperature of water samples were found to be in the range of 38 to 89 °C, pH values were in the range of 6.31 to 7.91, while conductivity values were in the range of 281 to 1624 μS/cm. With respect to water samples, it was discovered that boron and arsenic values in 13 hot springs, calcium values in 5 hot springs, barium values in 2 hot springs, manganese values in 1 hot spring and phosphorus value in 2 hot springs in autumn and summer, potasssium and lithium values in all hot springs were higher than the standard values of WHO and TSE-266. Thermal water from the research site were considered to be used in broader fields and contribute more to economy, while it was concluded that high values should be taken into account during use.